Analysis of Factors Affecting the Nutritional Status of School-Age Children at SDN 31 Pasar Ambacang Padang - Nova Fridalni; Sandra Hardini; Vira Oktaviani; Ratna Indah Sari Dewi; Etri Yanti (STIKES Syedza Saintika Padang, 2025)
The nutritional status of school-age children is an important indicator in determining the quality of future human resources. This study aimed to identify factors associated with the nutritional status of school-age children at SDN 31 Pasar Ambacang, Padang City. The research used a quantitative method with a correlational design and a cross-sectional approach. The population consisted of all students at SDN 31 Pasar Ambacang and their mothers, with 68 respondents selected using proportionate random sampling. Data were collected through anthropometric measurements (body weight and height) and questionnaires on children's eating patterns and mothers’ nutritional knowledge, then analyzed using the Chi-Square test (p < 0.05). The results showed that most children had poor nutritional status (72.1%), unhealthy eating patterns (76.5%), no breakfast habits (64.7%), and low maternal nutritional knowledge (64.7%). Statistical analysis revealed significant relationships between eating patterns (p=0.003), breakfast habits (p=0.001), and mothers’ nutritional knowledge (p=0.022) with children's nutritional status. The study concluded that healthy eating patterns, regular breakfast habits, and adequate maternal nutritional knowledge contribute to optimal nutritional status among school-age children.Keywords: Nutritional status; Eating patterns; Breakfast habits; Maternal knowledge